Reaching out to the American middle class: Peggy Noonan’s conservatism - Luc BENOIT A LA GUILLAUME (E-REA)
Since the 1990s, Peggy Noonan’s writings have translated conservative ideas into articles and bestselling books for the wider American public. In a less abrasive way than Rush Limbaugh or Ann Coulter, she expresses the hopes and fears of the Reagan Democrats. This article analyzes Noonan’s ambivalent rhetoric, which mirrors the ambivalent attitudes of parts of America’s embattled middle class.